2017
DOI: 10.1007/s11356-017-8772-4
|View full text |Cite
|
Sign up to set email alerts
|

Resilience potential of an Indian Ocean reef: an assessment through coral recruitment pattern and survivability of juvenile corals to recurrent stress events

Abstract: Coral reefs are degraded by the synergistic action of climate and anthropogenic stressors. Coral cover in the Palk Bay reef at the northern Indian Ocean largely declined in the past decade due to frequent bleaching events, tsunami and increased fishing activities. In this study, we carried out a comparative assessment to assess the differences in the recovery and resilience of three spatially distant reefs viz. Vedhalai, Mandapam and Pamban along Palk Bay affected by moderate, severe and low fishing pressure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The density of juvenile corals recorded in our study was 0.89-3.73 colonies/m 2 , which is comparable to that of the Palk Bay reef in the northern Indian Ocean [17] but is much lower than that of several reef sites in the Indo-Pacific region, in which the juvenile coral density at some reef sites was over 50 colonies/m 2 [48,49]. Variation in the juvenile coral density between the study sites of Mu Ko Chumphon and Ko Losin was obviously shown in this study.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The density of juvenile corals recorded in our study was 0.89-3.73 colonies/m 2 , which is comparable to that of the Palk Bay reef in the northern Indian Ocean [17] but is much lower than that of several reef sites in the Indo-Pacific region, in which the juvenile coral density at some reef sites was over 50 colonies/m 2 [48,49]. Variation in the juvenile coral density between the study sites of Mu Ko Chumphon and Ko Losin was obviously shown in this study.…”
Section: Discussionsupporting
confidence: 79%
“…Sediment loaded from coastal development and tourism impacts should be carefully mitigated for passive coral reef restoration. A high diversity of healthy corals in a coral reef ecosystem is an important factor for enhancing reef resilience potential because it occupies the reef substrates and inhibits the settlement of other benthic organisms that are coral competitors [17]. The coral communities at Ko Kula and Ko Ngam Yai also require an adequate supply of coral larvae from other coral reefs in the Gulf of the Thailand to enhance their coral diversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ultimately for long-term reef persistence, what matters is 'demographic connectivity', encompassing coral reproduction frequency and success, recruitment and postsettlement mortality processes. Utilising these processes to derive novel reef resilience metrics has been suggested during the last decade [91][92][93], and studies are increasingly incorporating these aspects into resilience assessments [94][95][96]. Continuing to focus on assessing reproduction and recruitment as fundamental ecological processes will facilitate managing for reef resilience more than traditional assessments of ecosystem state and condition [97].…”
Section: Coral Reef Site Resiliencementioning
confidence: 99%